Correlation analysis between patent ductus arteriosus and bronchopulmonary dysplasia in premature infants - Hao Luo; Yibo Liu; Chongbing Yan; Bowen Weng; Laxiu Zhao; Cheng Cai (Italian Journal of Pediatrics)
Abstract Background To evaluate the correlation between patent ductus arteriosus (PDA) and bronchopulmonary dysplasia (BPD) in premature infants. Methods Retrospective analysis was performed on preterm infants with a gestational age(GA) of less than 32 weeks from 2019 to 2021. PDA premature infants with BPD ( N = 70 ) or not ( N = 224) were enrolled for multivariate logistic regression exploring independent risk factors for BPD in PDA preterm infants. The nomogram model was employed for exhibiting risk factors and receiver operating characteristic curve (ROC) was used to evaluate model performance. Results (1) GA, birth weight (BW) and Apgar (5 min) score in BPD group were significantly lower than non-BPD group (p < 0.0001). (2) BPD group had a higher utilization rate of pulmonary surfactant, more infants receiving oxygen therapy through nasal catheters, and a longer oxygen therapy duration (p < 0.0001). (3) The proportion of haemodynamically significant patent ductus arteriosus(hsPDA)in BPD group was significantly higher than that in non-BPD group (p < 0.05). (4) The incidence of anemia and pulmonary hypertension in BPD group infants was significantly higher than that in non-BPD group (100% and > 50% in BPD, respectively, p < 0.05). (5) The goodness of fit test of calibration curve showed χ2 = 7.136, p = 0.522, and area under curve (AUC) was 0.799. Conclusions GA, BW and PDA diameter were independent risk factors for PDA merged with BPD. The smaller GA, the lower BW, the larger PDA diameter and the lower Apgar score (5 min), and the higher the risk of BPD in PDA infants.